Enhancing Resistance of Hill Cipher using Columnar and Myszkowski Transposition - Bhowmick, Anirban; Geetha, M (International Journal of Computer Sciences and Engineering, 2015)
Researchers are regularly trying to figure out secure encryption algorithms so that the data transmitted over the computer networks are not intercepted by an unwanted entity.. The two methods to encrypt data are- Transposition and Substitution. Transposition refers to changing the position of characters in a given text. On the other hand, substitution is the process of replacing each character of the plaintext with some other character. One main concern area is to the existing encryption system to overcome the flaws in them.